Percutaneous ethanol injection therapy is comparable to radiofrequency ablation in hepatocellular carcinoma smaller than 1.5 cm: A matched case–control comparative analysis. Issue 35 (August 2016) - Yu, Su Jong; Yoon, Jung-Hwan; Lee, Jeong Min; Lee, Jae Young; Kim, Se Hyung; Cho, Young Youn; Yoo, Jeong-Ju; Lee, Minjong; Lee, Dong Hyeon; Cho, Yuri; Cho, Eun Ju; Lee, Jeong-Hoon; et al.
Abstract : Abstract: Although percutaneous ethanol injection therapy (PEIT) is best indicated for patients with small hepatocellular carcinoma (HCC), the survival advantage of PEIT needs confirmation in real-world practice. This study was approved by the institutional review board, and the informed consent was waived. The study included 535 consecutive patients with newly diagnosed early stage (Barcelona Clinic Liver Cancer [BCLC] 0 or A) HCC who underwent initially radiofrequency ablation (RFA) (n = 288) or PEIT (n = 247) from January 2005 to December 2010. The primary outcome was overall survival (OS) and the secondary outcome was time to progression (TTP). The longest diameters of tumors of the groups differed significantly and larger for RFA group than PEIT group ( P < 0.001; 1.94 ± 0.65 cm vs 1.60 ± 0.50 cm, respectively). The 5-year OS rates were 72.2% in the RFA group and 67.4% in the PEIT group ( P = 0.608). Even after propensity score matching, OS rates between the 2 groups were similar (5-year OS: 72.8% with RFA [n = 175] and 68.0% with PEIT [n = 175]) ( P = 0.709). Moreover, in patients with the longest diameter of tumors (⩽1.5 cm), multivariate Cox regression analysis showed that the treatment modality was not a significant prognosticator for OS (hazard ratio [HR], 1.690; 95% confidence interval [CI], 0.828–3.449; P = 0.149) and time to progression (HR, 1.160; 95% CI, 0.773–1.740; P = 0.474). PEIT and RFA show equal effectiveness in treating HCCs <1.5 cm in terms of OS and time to progression. Abstract : Supplemental Digital Content is available in the text